Social calls of flying big brown bats (Eptesicus fuscus) - Wright, Genevieve S.; Chiu, Chen; Xian, Wei; Moss, Cynthia F.; Wilkinson, Gerald S. (Frontiers in Physiology, 2013)
Vocalizations serving a variety of social functions have been reported in many bat species (Order Chiroptera). While echolocation by big brown bats (Eptesicus fuscus) has been the subject of extensive study, calls used by this species for communication have received comparatively little research attention. Here, we report on a rich repertoire of vocalizations produced by big brown bats in a large flight room equipped with synchronized high speed stereo video and audio recording equipment. Bats were studied individually and in pairs, while sex, age, and experience with a novel foraging task were varied. We used Discriminant Function Analysis to classify six different vocalizations that were recorded when two bats were present. Contingency table analyses revealed a higher prevalence of social calls when males were present, and some call types varied in frequency of emission based on trial type or bat age. Bats flew closer together around the time some social calls were emitted, indicating that communicative calls may be selectively produced when conspecifics fly near one another. These findings are the first reports of social calls from flying big brown bats and provide insight into the function of communicative vocalizations emitted by this species.